2019
DOI: 10.1016/j.jnucmat.2018.12.021
|View full text |Cite|
|
Sign up to set email alerts
|

Density functional theory calculations of self- and Xe diffusion in U3Si2

Abstract: Peer reviewed versionCyswllt i'r cyhoeddiad / Link to publication Dyfyniad o'r fersiwn a gyhoeddwyd / Citation for published version (APA):

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 49 publications
5
30
0
Order By: Relevance
“…U 3 Si 2 has ultrahigh thermal conductivity and high uranium-containing density among uranium silicon compounds, which has attracted many researchers' attentions. 10,12,13 Due to poor mechanical performance and antioxidant capacity, alloying the U 3 Si 2 is an effective solution for further application within light water reactors. 14 Wood et al 15 studied the effect of adding Al elements into U 3 Si 2 on their performance through thermal reanalysis, and the investigation showed that U 3 Si 2 oxidation behavior could be postponed, which conrmed that U 3 Si 2 antioxidant resistance was improved by adding Al elements.…”
Section: Introductionmentioning
confidence: 99%
“…U 3 Si 2 has ultrahigh thermal conductivity and high uranium-containing density among uranium silicon compounds, which has attracted many researchers' attentions. 10,12,13 Due to poor mechanical performance and antioxidant capacity, alloying the U 3 Si 2 is an effective solution for further application within light water reactors. 14 Wood et al 15 studied the effect of adding Al elements into U 3 Si 2 on their performance through thermal reanalysis, and the investigation showed that U 3 Si 2 oxidation behavior could be postponed, which conrmed that U 3 Si 2 antioxidant resistance was improved by adding Al elements.…”
Section: Introductionmentioning
confidence: 99%
“…6 A number of theoretical studies on the behavior of ssion products in U-Si compounds has been reported, including H, H 2 , Xe, Zr, Sr, Ba, Nd, and Ce. [6][7][8][9][10][11][12][13][14][15] Helium, one of the main gases in LWR, has a low diffusion barrier within materials, such as metals and even the MAX phase Ti 3 AlC 2 ; 16 thus, it tends to aggregate and form bubbles within these materials. However, the He gas behavior in U 3 Si 5 , which has one of the very important fuel performance behaviors in U 3 Si 5 , are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…We rely on density functional theory calculations to provide initial estimates of these rates. The full results of the DFT calculations are presented elsewhere [35]. Here, we briefly outline the computational methodology and the key results used in the fission gas model presented in Section 3.…”
Section: Density Functional Theory Calculations Of Defects and Fission Gas Propertiesmentioning
confidence: 99%
“…The migration barriers of vacancies and Xe atoms were calculated for a range of possible mechanisms, see Ref. [35] for additional details. Here we are only concerned with the fastest diffusion rate of Xe and uranium vacancies.…”
Section: Density Functional Theory Calculations Of Defects and Fission Gas Propertiesmentioning
confidence: 99%